Gold-Catalyzed One-Step Practical Synthesis of Oxetan-3-ones from Readily Available Propargylic Alcohols - Ye, Longwu; He, Weimin; Zhang, Liming (Journal of the American Chemical Society, 2010)
A general solution for the synthesis of various oxetan-3-ones is developed. This reaction uses readily available propargylic alcohols as substrates and proceeds without the exclusion of moisture or air (“open flask”). Notably, oxetan-3-one, a highly valuable substrate for drug discovery, can be prepared in one step from propargyl alcohol in a fairly good yield. The facile formation of the strained oxetane ring provides strong support for the intermediacy of α-oxo gold carbenes. This safe and efficient generation of gold carbenes via intermolecular alkyne oxidation offers a potentially general entry into α-oxo metal carbene chemistry without using hazardous diazo ketones.